Research on the impact of personality traits on attitude towards risk in investment among individual investors in Vietnam - Mai, Thi Dung; Ngo, Hoang Nam; Vuong, Hung Nam (International Journal of Scientific Research and Management (IJSRM), 2025)
The purpose of this study is to explore the impact of personality traits on attitude towards risk in investment among individual investors in Vietnam. This paper applies the Big Five Personality Traits model (Costa, P. T., & McCrae, R. R., 1992), which includes five dimensions: Neuroticism, Extraversion, Openness to Experience, Agreeableness, and Conscientiousness. The research findings indicate that “Extraversion” (EXT) and “Openness to Experience” (OPE) positively influence risk acceptance attitudes; the “Neuroticism” (NEU) trait exerts the strongest negative impact, suggesting that individuals with high anxiety levels tend to be risk-averse in their investments. Meanwhile, “Conscientiousness” (CNS) and “Agreeableness” (ARG) show a mild positive influence on risk tolerance. These findings align with a sample predominantly composed of young investors and the context of a diversifying investment landscape in Vietnam.